Synthesis of tetrafluorinated piperidines from nitrones via a visible-light-promoted annelation reaction - Supranovich, Vyacheslav I (Beilstein J Org Chem, 2020)
A method for the one-step construction of 3,3,4,4-tetrafluorinated piperidines from nitrones and readily accessible tetrafluorinated iodobromobutane is described. The reaction requires an excess amount of ascorbic acid as the terminal reductant and is performed in the presence of an iridium photocatalyst activated by blue light. The annelation is a result of a radical addition at the nitrone, intramolecular nucleophilic substitution, and reduction of the N–O bond.